PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN GOJEK DI UIN RADEN INTAN LAMPUNG - BENI ANTOMI (Business and Enterpreneurship Journal (BEJ), 2023)
This study aims to determine the effect of price, promotion, and service quality on customer satisfaction of GO-JEK online ojek transportation (study on customers at UIN RIL). The independent variables in this study are promotion, and service quality, while the dependent variables in this study are customer satisfaction. The population used in this study were students at UIN RADEN INTAN LAMPUNG who used GO-JEK services. The samples used in this study were 51 samples. The sampling technique in this study was to use purposve sampling technique. The data of this study is in the form of primary data sourced from questionnaires and data analysis using multiple regression analysis with the help of SPLS 3 software. The results of this study show that the promotion variable partially has a positive and significant effect on customer satisfaction, hence hypothesis 1 is accepted. The promotion variable partially has a positive and significant effect on customer satisfaction, so hypothesis 2 is accepted.  Keywords : Service Quality, Customer Satisfaction, and Customer Loyality